Relative strength of the Antarctic Circumpolar Current and Atlantic Meridional Overturning Circulation - Marshall, D; Johnson, H (Taylor and Francis, 2017)
A simple relationship, based on thermal wind balance, is derived that relates the relative strength of the Antarctic Circumpolar Current (ACC) and Atlantic Meridional Overturning Circulation (AMOC) to the ratios of three depth scales: the e-folding depth of the global stratification, the depth of maximum overturning streamfunction and the maximum depth of the ACC. For realistic values of these depth scales, the relationship predicts a factor 8 ± 4 difference in the volume transports of the ACC and AMOC, consistent with the observation-based ratio of 8 ± 2.